ANALYSIS RISK MAPPING OF BATIK KARAWANG DISTRIBUTION TO EXPAND DISTRIBUTION COVERAGE - muhamad sayuti (Journal of Industrial Engineering and Halal Industries)
Tourism is a resource that can be developed in Indonesia because it has a positive impact on economic growth both locally and nationally which can increase regional income so that local community empowerment and poverty alleviation can be done. One of the efforts in developing the local economy is by making regional superior products such as the development of batik that has been internationally recognized by UNESCO as Indonesia's cultural heritage. Karawang has distinctive batik and is different from batik from other regions, so this batik is admired by the Karawang community itself. The distribution of Karawang batik still has many obstacles both in terms of regional conditions, the number of craftsmen and branding that are not yet strong. This research focuses on re-mapping the flow of Karawang batik distribution with reference to risk management. This research is very important to improve the flow distribution of Karawang batik, so that it will make the distribution coverage of this batik even wider. This study uses a mapping method  distribution flow, taking into account the risk management. The risk management itself uses a Risk Register map, so that the risk exposure from Karawang batik will be increasingly clear and is expected to make mitigation and minimize risk. After conducting a causal analysis and risk map, several proposals were extended to expand the scope of marketing, including the Religious Community, the Government Organizations, Banking Companies, Private Companies, Motor and Car Commodities. The proposal is expected to be implemented and have a positive influence. Furthermore, it will be monitored once a year to see the changes